The differences of hand grip strength test among racquet sports and team sports / Ahmad Mukhlis Abd Aziz - Abd Aziz, Ahmad Mukhlis (2019)
A study of maximum isometric strength that involve hand and forearm muscles among different type of sports and also among racquet sports and team sports. The maximum isometric strength were measured by using hand grip strength test. The test way completed using a dynamometer which measured in kilograms. These study purposely was made to identify the performance different among difference type of sport on hand grip strength with additional purpose by measuring the hand grip strength among individual sports and team sports. The cross sectional research design was used in this study. Subject were 60 student athletes from UiTM that involved in KARISMA 2018. Six different sports consist of 10 subject and the divided into racquet sport and team sports. The statistical analysis of this study were one-way ANOVA for multiple comparison to identify the different between sport and one sample t test were used to compare between individual sports and team sports. This study show that hockey have the highest hand grip strength (M=38.43, sd= 5.39). This study also show that team sport higher than individual sports in hand grip strength test for left hand (M=37.12, sd=5.06) for the right hand (M=38.67, sd=4.29). Conclusion, this study may develop training program focusing on strength that can improve the performance indicator as well as the hand grip which is the important in different sports